Identification of a cluster of residues in transmembrane segment 6 of domain III of the cockroach sodium channel essential for the action of pyrethroid insecticides - Du, Yuzhe (2009)
A phenylalanine residue (Phe(1519)) in the sixth transmembrane segment of domain III (IIIS6) of the cockroach BgNa(v) sodium channel is required for the binding and action of pyrethroids. However, whether or not other residues in IIIS6 participate in the action of pyrethroids remains to be determined. In the present study, we conducted a systematic analysis of 20 residues in IIIS6 of the BgNa(v) channel using alanine-scanning mutagenesis. Our results show that alanine substitutions of four residues, Ile(1514), Gly(1516), Phe(1518) and Asn(1522), altered sodium channel sensitivity to pyrethroid insecticides. Whereas the G1516A, F1518A and N1522A substitutions diminished sodium channel sensitivity to all seven pyrethroids examined, including four type I (lacking the α-cyano group at the phenoxybenzyl alcohol) and three type II (containing the α-cyano group) pyrethroids, the I1514A substitution enhanced sodium channel sensitivity to four type I and type II pyrethroids that contain the phenoxybenzyl alcohol only. We also show that alanine/lysine substitutions of Leu(1521) and Ser(1517) affected the action of BTX (batrachotoxin), but not pyrethroids. In the K(v)1.2-based homology model of the open sodium channel, side chains of Ile(1514), Phe(1518) and Asn(1522) are exposed towards helix IIS5 and linker IIS4–IIS5, which contain previously identified pyrethroid-interacting residues, whereas Ser(1517) and Leu(1521) face the inner pore where the BTX receptor is located. Thus the present study provides further evidence for structural models in which pyrethroids bind to the lipid-exposed interface formed by helices IIIS6, IIS5 and linker helix IIS4–IIS5, whereas BTX binds to the pore-exposed side of the IIIS6 helix.